Transurethral Radiofrequency Collagen Denaturation for Treatment of Female Stress Urinary Incontinence: A Review of the Literature and Clinical Recommendations - James Chivian Lukban (Obstetrics and Gynecology International)
Stress urinary incontinence is a prevalent condition in women with a significant negative effect on quality of life. Intervention includes behavioral modification, intravaginal devices, pelvic floor muscle exercises, biofeedback, functional electrical stimulation, and surgical procedures. We will review a new in-office procedure for the treatment of SUI that may serve as a viable nonsurgical option.